ELASTOGRAPHIC CHARACTERISTICS OF THE METACARPAL TENDONS IN HORSES WITHOUT CLINICAL EVIDENCE OF TENDON INJURY. Issue 1 (17th September 2013) - Lustgarten, Meghann; Redding, W. Rich; Labens, Raphael; Morgan, Michel; Davis, Weston; Seiler, Gabriela S.
<x xml:space="preserve">Abstract</x> Tendon and ligament injuries are common causes of impaired performance in equine athletes. Gray‐scale ultrasonography is the current standard method for diagnosing and monitoring these injuries, however this modality only provides morphologic information. Elastography is an ultrasound technique that allows detection and measurement of tissue strain, and may provide valuable mechanical information about equine tendon and ligament injuries. The purpose of this study was to determine the feasibility, reproducibility, and repeatability of elastography; and to describe elastographic characteristics of metacarpal tendons in sound horses. Nineteen legs for 17 clinically sound horses without evidence of musculoskeletal pathology were included. Elastographic images of the superficial and deep digital flexor tendons and the branches of the suspensory ligament (tendon of the interosseous muscle) were described quantitatively and qualitatively. There was no statistically significant difference between operators (P = 0.86) nor within operators (P = 0.93). For qualitative assessments, reproducibility (0.46) was moderate and repeatability (0.78) was good. Similar to human Achilles tendons, equine tendons were classified as predominantly hard using elastography. There was no statistically significant difference in stiffness of the flexor tendons (P = 0.96). No significant difference in stiffness was found with altered leg position during standing (P = 0.84) and while nonweight bearing (P = 0.61). The flexor tendons were softer when imaged in longitudinal versus transverse planes (P < 0.01) however, the suspensory branches were not (P = 0.67). Findings supported future clinical application of elastography as a noninvasive "stall‐side" imaging modality for evaluation of the tendons and ligaments of the distal forelimb in horses.